Ruptured tubal stump pregnancy: a rare case report - Mukherjee, Shubhra; Maheshwari, Charu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ectopic pregnancy occurring in tubal stump is exceedingly rare. The frequency of tubal stump pregnancy is approximately 0.4 % of all pregnancies. Early diagnosis and management is crucial for prevention of morbidity and mortality We reported a case of ruptured tubal stump pregnancy managed successfully in our institute.